2017
DOI: 10.2217/cnc-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

White matter changes in patients with mild traumatic brain injury: MRI perspective

Abstract: This review focuses on white matter (WM) changes in mild traumatic brain injury (mTBI) as assessed by multimodal MRI. All the peer reviewed publications on WM changes in mTBI from January 2011 through September 2016 are included in this review. This review is organized as follows: introduction to mTBI, the basics of multimodal MRI techniques that are potentially useful for probing the WM integrity, summary and critical evaluation of the published literature on the application of multimodal MRI techniques to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 170 publications
(171 reference statements)
4
54
2
1
Order By: Relevance
“…Despite reports of alterations in diffusivity measures following concussion, the direction of these changes has been a source of substantial disagreement (Dodd et al, 2014;Eierud et al, 2014;Honce, Nyberg, Jones, & Nagae, 2016;Moore, Kay, & Ellemberg, 2018;Narayana, 2017;Schmidt et al, 2018). Most dMRI studies have focused on adult or mixed age samples in the acute periods following injury, and very few studies have focused on more chronic time points (i.e., greater than 3 or 6 months post-concussion).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite reports of alterations in diffusivity measures following concussion, the direction of these changes has been a source of substantial disagreement (Dodd et al, 2014;Eierud et al, 2014;Honce, Nyberg, Jones, & Nagae, 2016;Moore, Kay, & Ellemberg, 2018;Narayana, 2017;Schmidt et al, 2018). Most dMRI studies have focused on adult or mixed age samples in the acute periods following injury, and very few studies have focused on more chronic time points (i.e., greater than 3 or 6 months post-concussion).…”
Section: Introductionmentioning
confidence: 99%
“…However, increased FA has also been observed and may be indicative of cytotoxic edema acutely after injury (Wilde et al, 2008) or a loss of crossing fibers chronically after injury (Henry et al, 2011;Orr et al, 2016). Though often reported in terms of FA, similar inconsistent findings for measures of MD, AD, and RD in the corpus callosum have been reported as well (Eierud et al, 2014;Honce et al, 2016;Moore et al, 2018;Narayana, 2017;Schmidt et al, 2018). Unfortunately, few studies have utilized dMRI in pediatric-only populations with concussion.…”
Section: Introductionmentioning
confidence: 99%
“…Listening engages cognitive networks and the precision of sound processing is linked to cognitive skills as attention and working memory (Kraus et al, 2016). These processes activate neural circuits within temporal and frontal cortices (Stanley et al, 2015), which are the areas of neocortex most susceptible to injury in a concussion (Narayana, 2017). Also, multimodal MRI studies identified that corpus callosum (CC), particularly splenium, is the most commonly affected white matter tract in mTBI (Aoki, Inokuchi, Gunshin, Yahagi, & Suwa, 2012) and that CC white matter changes can be associated with graded deficits in working memory (Prins, Hales, Reger, Giza, & Hovda, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The other indicators of ongoing neuropathology after a concussion are biomarkers such as plasma tau changes (Gill, Merchant‐Borna, Jeromin, Livingston, & Bazarian, ) or white matter changes (Narayana, ). Recently, Kraus et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation